Larval development of mandi-pintado Pimelodus britskii (Siluriformes: Pimelodidae) - Almeida, Mara C. [UNESP]; Message, Hugo J.; Sanches, Paulo V.; Baumgartner, Dirceu; Bombardelli, Robie A.; Baumgartner, Gilmar; Francisco, Langeani [UNESP] (Wiley-Blackwell, 2019)
This study investigated the morphology, morphometric and meristic characters of 117 larval Pimelodus britskii showing early development of head, eye, barbel and snout. Body and mouth pigmentation increased throughout development; the mouth was ventrally situated in the yolk-sac stage, becoming subterminal afterwards, and an embryonic fin was visible in all four stages observed. Post-flexion larval P. bristskii are distinguished from larval P. ortmanni by having 47-50 myomeres (v. 36).
Keywords: Brazil; catfish; ichthyoplankton; Iguacu River; larvae; morphometry